LITERASI KAWASAN SOSIOLOGI MAHASISWA DALAM MEMPERSIAPKAN KARYA AKHIR PROGRAM STUDI PENDIDIKAN SOSIOLOGI FKIP UNTAN - Rustiyarso, Rustiyarso (Universitas Tanjungpura, 2017)
Â Â AbstractThis study aimed to describe the education of sociology departement literacy used by students of sociology of education in preparing the final work in FKIP Tanjungpura University of. The method used is descriptive method survey form with a qualitative approach. Data collected by the indirect communication. Data collection tool used is a questionnaire and documentation in the form outline and design student research. The population of this study were all students of sociology of education that has been qualified in completing course credits a number of 110-115 credits and be eligible to apply for the title of the research to the academic supervisor. The research proves that students in general education courses sociology